Utilisation of biochar and superabsorbent polymers for soil amendment. (28th March 2013) - Ekebafe, M.O.; Ekebafe, L.O.; Maliki, M.
The application of superabsorbent polymers (SAPs) and/or biochars to stressed lands offer solutions to several critical ecological, energy and economic challenges posed by degraded lands due to human activities. These substances are like, 'artificial humus' as they are hydrophilic and contain carboxylic groups (SAPs) which enable them to bind cations and water, and sequester carbon from air to reverse global warming (biochars). Several research studies using these substances point to their ability to increase the plant-available water in the soil which enables the plants to survive longer with water shortage, increase soil fertility and agricultural yields, improve soil structure, aeration and water penetration, reduce use of synthetic fertilisers and pesticides, reduce nitrous oxide and methane emission from soil, reduce nitrate and farm chemicals leaching into watersheds, convert green and brown wastes into valuable resources, and reduce the evapotranspiration rate of the plants. SAPs and biochars induce a significantly higher growth rate in plants; they bind heavy metals and mitigate their action on plants as well as mitigate the effects of salinity. This paper reviews what is known about these claims and considers the wider environmental implications of the adoption of these processess. The intention is not just to summarise the current knowledge but also to identify gaps that require further research.